Association between renal function and diabetic retinopathy: a mediation analysis of geriatric nutritional risk index - Youran Cai; Wanlu Qiu; Xiao Ma; Yuanting Yang; Ting Tang; Yuying Dong; Jian Chen; Qing Zhou (Diabetology & Metabolic Syndrome)
Abstract Background Diabetes retinopathy (DR) is a prevalent microvascular complication of type 2 diabetes mellitus (T2DM). This study investigated the correlation between renal function and DR, as well as the potential mediating role of the geriatric nutritional risk index (GNRI). Method We classified 1122 adults with T2DM aged ≥ 40 years from the National Health and Nutrition Examination Survey database (2005–2008) into 2 groups: those with DR and those without DR. We used multivariate logistic regression analysis and restricted cubic spline (RCS) model to explore the relationship between renal function indicators and DR. Additionally, we analyzed the mediating impact of GNRI on renal function and DR. Result After accounting for all covariates, the weighted multivariate analysis revealed significant associations between renal function markers and DR. Specifically, creatinine, albumin, blood urea nitrogen, and serum uric acid to creatinine ratio (SUACr) were significantly correlated with DR in serum examination, while creatinine was the only marker correlated with DR in urine. GNRI was negatively correlated with DR (odds ratio 0.94, 95% CI 0.92–0.99). Weighted linear regression showed a negative association between SUACr and GNRI (β = 0.37; 95% CI 0.12–0.62). The RCS analysis showed a nonlinear association between serum creatinine and DR (P non-linear = 0.013). GNRI mediated 14.4% of the relationship between SUACr and DR. Conclusion Our study adds to previous research by analyzing the associations between renal function indicators and DR. Furthermore, we highlight the mediating effect of GNRI, suggesting its potential utility as a predictive and treatment index for assessing renal function and DR.